2020
DOI: 10.1017/s1478951520000383
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and quality of life in women with breast cancer: The role of hope and educational attainment

Abstract: Objective This study investigated relationships among spirituality, hope, and overall quality of life in Muslim women with breast cancer in Malaysia. Method A cross-sectional descriptive design with a convenience sample of 145 Malay patients was used. The mediating role of hope in the relationship between spirituality and quality of life as well as the moderating effect of education level on the spirituality hope link were examined. Results Participants with higher self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 58 publications
0
25
0
1
Order By: Relevance
“…Higher educational attainment has been known all over the world to be significantly related to women’s awareness of breast cancer [ 33 , 36 38 ]. In all these studies, it was shown that women’s educational status increased their awareness and the chance of using screening services [ 13 , 33 , 36 38 ]. Women of higher educational status can read and comprehend health-related information compared to the non-educated women.…”
Section: Discussionmentioning
confidence: 99%
“…Higher educational attainment has been known all over the world to be significantly related to women’s awareness of breast cancer [ 33 , 36 38 ]. In all these studies, it was shown that women’s educational status increased their awareness and the chance of using screening services [ 13 , 33 , 36 38 ]. Women of higher educational status can read and comprehend health-related information compared to the non-educated women.…”
Section: Discussionmentioning
confidence: 99%
“…There is an assumption that believing in “spiritual life” can reduce the fear of facing death ( Bower et al, 2015 ; Puchalski et al, 2018 ; Garduño-Ortega et al, 2021 ). While China is not a religious country, many Chinese people are spiritual and incorporate Confucianism, Taoism, and Buddhism into their daily lives ( Huang and You, 2015 ; Pahlevan Sharif et al, 2021 ). The study illustrated by the MBC women participants’ deep reflection on the value of life arose from their experience of the misery inflicted by their cancer journey, a source of inner strength and peacefulness.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the high cost of these reconstructive surgeries and implanting internal prostheses, women who turn to these methods have a better financial status, which supports our previous finding. Perceived body image influences participants' perceptions of concepts such as spirituality and hope [ 31 ].…”
Section: Discussionmentioning
confidence: 99%